SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN BARU TEBUIRENG ONLINE MENGGUNAKAN METODE MULTI OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS (MOORA) - Amirudin Hidayatulloh , Muhammad; Setyo Permadi , Ginanjar (Inovate, 2024)
Employees are one of the most important assets owned by a company in its efforts to maintain survival, development, ability to compete and earn profits. researchers are interested in conducting research at the Tebuireng online Agency using the Multi-Objective Optimizaton on Basis of Ratio Analysis (MOORA) method. The application of the MOORA method is expected to provide benefits to obtain optimal alternative values from a number of alternatives and certain criteria which are then followed by a ranking process. Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) is a multi-objective system that optimizes two or more conflicting attributes simultaneously. This method is applied to solve problems with complex mathematical calculations. researchers created a website-based system to make it easier to make decisions easily and get results that match what the Tebuireng online agency wants. This decision support system is only a system to assist decision makers in determining the optimal choice, not a decision making system. Keywords: Employee, Decision Support System, Moora, Website